2011
DOI: 10.4038/jccp.v41i2.3766
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and other features of a cohort of adult Sri Lankans presenting with upper gastrointestinal bleeding (UGIB)

Abstract: Results: There were 342 (24%) upper GI bleeders. The mean age of presentation was 55.5 years +/-14.4 SD. A high proportion was seen between 50-70 years of age. Sex distribution was, male:female = 229:114 (2:1). 45% have presented with haematemesis, 31% with malaena, and 24% with both. Endoscopy showed the presence of severe antral gastritis and duodenitis, oesophageal varices, oesaphagitis, erosive gastropathy, portal hypertensive gastropathy, pangastritis and peptic ulcer disease in 38%, 35%, 28%, 28%, 20%, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In this study, the median age of the studied patients was 45 years, and males outnumbered females (approximately 2:1 ratio). This finding coincides with several reports obtained from a prospective study on patients with UGIB in Iceland [9], a multicenter study in USA [8], a cohort of adult Sri Lankans [10], and a tertiary care center in Nepal [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the median age of the studied patients was 45 years, and males outnumbered females (approximately 2:1 ratio). This finding coincides with several reports obtained from a prospective study on patients with UGIB in Iceland [9], a multicenter study in USA [8], a cohort of adult Sri Lankans [10], and a tertiary care center in Nepal [11].…”
Section: Discussionsupporting
confidence: 92%
“…However, duodenal and gastric ulcers accounted for 43% of patients with UGIB in Nepal, followed by variceal bleeding in 23% of cases [ 11 ]. Another study in Sri Lanka identified severe erosive antral gastritis and duodenitis as the most frequent causes of UGIB, while chronic duodenal and gastric ulcers were less frequent [ 10 ]. The predominance of non-variceal causes has also been stated in several studies from different geographical areas [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Another study in Sri Lanka identified severe erosive antral gastritis and duodenitis as the most frequent causes of UGIB, while chronic duodenal and gastric ulcers were less frequent. 19 Peptic ulcer disease 35% followed by oesophageal/gastric Varices 20% was most common endoscopic findings in another similar studies. 20…”
Section: Discussionmentioning
confidence: 73%
“…61 Satarasinghe and colleagues in a series of 1500 patients found alcohol was a contributory factor in one third of gastrointestinal bleeding (IGIB) patients. 63…”
Section: Smoking and Alcoholmentioning
confidence: 99%